2010
DOI: 10.1097/01.aids.0000391021.18284.12
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to implementation of isoniazid preventive therapy in HIV clinics: a qualitative study

Abstract: Barriers to the widespread use of IPT primarily derived from healthcare workers, in particular, lack of experience among physicians. In addition to overcoming operational barriers, a change in healthcare worker perception is needed if IPT is to be widely used; we suggest local clinical opinion leaders could help achieve this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
173
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(184 citation statements)
references
References 6 publications
8
173
0
3
Order By: Relevance
“…Meta-analyses of randomized controlled trials have shown that IPT reduces the risk of active TB by 33% in people living with HIV, irrespective of skin test result, and by up to 64% in those with a positive tuberculin skin test [20,21]. Despite the substantial amount of clinical research that showed the benefits of IPT among people living with HIV, several barriers and operational challenges have hampered its roll out [22].…”
Section: Key Areas Of Operational Researchmentioning
confidence: 99%
“…Meta-analyses of randomized controlled trials have shown that IPT reduces the risk of active TB by 33% in people living with HIV, irrespective of skin test result, and by up to 64% in those with a positive tuberculin skin test [20,21]. Despite the substantial amount of clinical research that showed the benefits of IPT among people living with HIV, several barriers and operational challenges have hampered its roll out [22].…”
Section: Key Areas Of Operational Researchmentioning
confidence: 99%
“…In Ivory Coast, the national guidelines do not recommend the use of IPT, owing to the concern that IPT may select resistant bacilli when given to patients with undiagnosed tuberculosis. 19,20 The Ministry of Health accepted its use within an experimental framework.…”
mentioning
confidence: 99%
“…Of the 2,305 TSTs performed, 1,053 (46%) were performed in indigenous populations; 831 (36%) were screenings in prisons, performed for training; and only 421 (18%) involved contacts of tuberculosis patients or priority populations, such as HIV-infected individuals. (16) In the indigenous populations, the TSTs resulted in 124 patients being treated for latent tuberculosis, a figure that is noteworthy Our analysis of TST use reveals a disconnect between guidelines and practice. Although scientific evidence of the importance of the TST and preventive treatment for latent tuberculosis has been collected for 18 years, this does not seem to be reflected in the number of TSTs performed in the various at-risk populations, in which the test should be administered on an annual basis, or in the number of individuals treated for latent tuberculosis.…”
Section: Discussionmentioning
confidence: 84%
“…Our survey revealed that there were no training courses for the health care workers at the specialized PCCs under study; among those observed for all of the priority municipalities that had TCPs and specialized PCCs. (16) Five screenings were performed in prisons, and one was performed at a military barracks. Those screenings were performed either in an attempt to identify contacts of tuberculosis patients or in order to provide technical training.…”
Section: Resultsmentioning
confidence: 99%